Ubi thesaurus tuus, ibi et cor tuum. Tadeusz Czacki in Ireneusz Jakubowski’s Research - Czech-Jezierska, Bożena Anna; Dębiński, Antoni (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Tadeusz Czacki was an outstanding activist and historian, who lived at the turn of the 18th century. He founded a famous secondary school in Krzemieniec, where teaching law (including Roman law) was an important part of education. Dr Ireneusz Jakubowski has published thirteen articles on Tadeusz Czacki and his perspective on the importance of Roman law in Polish legal history. The authors synthesised Ireneusz Jakubowski’s research on Tadeusz Czacki and his ideas about law, especially Roman law.